Transforming growth factor-β induces nerve growth factor expression in pancreatic stellate cells by activation of the ALK-5 pathway - Haas, Stephan; Fitzner, Brit; Jaster, Robert; Wiercinska, Eliza; Gaitantzi, Haristi; Jesenofsky, Ralf; Löhr, J.-Matthias; Singer, Manfred V.; Dooley, Steven; Breitkopf-Heinlein, Katja (Growth factors, 2009)
Nerve growth factor (NGF), a survival factor for neurons enforces pain by sensitizing nociceptors. Also in the pancreas, NGF was associated with pain and it can stimulate the proliferation of pancreatic cancer cells. Hepatic stellate cells (HSC) respond to NGF with apoptosis.Transforming growth factor (TGF)-β, one of the strongest pro-fibrogenic activators of pancreatic stellate cells (PSC) induced NGF and its two receptors in an immortalized human cell line (ihPSC) and primary rat PSC (prPSC) as determined by RT-PCR, western blot, and immunofluorescence. In contrast to HSC, PSC expressed both NGF receptors, although p75NTR expression was weak in prPSC. In contrast to ihPSC TGF-β activated both Smad signaling cascades in prPSC. NGF secretion was diminished by the activin-like kinase (ALK)-5 inhibitor SB431542, indicating the predominant role of ALK5 in activating the NGF system in PSC. While NGF did not affect proliferation or survival of PSC it induced expression of Inhibitor of Differentiation-1.We conclude that under conditions of upregulated TGF-β, like fibrosis, NGF levels will also increase in PSC which might contribute to pancreatic wound healing responses.